Histological and Morphological Study of Carcinoma Breast of Women - Aaya Hamid Al-Hakeem1 , Marwa Ahmed Meri1 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Previous studies have referred that the breast cancer, with particular histological traits, can be affected bythe reproductive factors. In the current study, we employed 30 breast cancer cases for women in age (15-55years) to study how factors such as microscopic screening, gross examination, as well as the age, can impacton histological type and grade of tumor. After the organ eradication from the patients, the tissue sampleswere picked, as fast as possible, and placed in 10% formalin directly. In such a way, we maintained thecells and cellular components in a situation that can be described as similar as possible to the living cellsand preserved the antigenicity in order to be processed without any modification. Samples were divideddepending on various factors, such as anatomical location, the nodal status, and tumor relationship tosurgical margin, weight, size, and age. Each sample was sectioned and fixed onto a private embeddingcassette to keep the tissue treatment. The histochemical stains, which is include the eosin and hematoxylin,had utilized to afford a disparity to tissue sections. We found that the majority of the 30 women with breastcancer were at age (31-40 years) and that 12 patients of them were involved left breast, while the other 18patients included right breast. In agreement with previous studies that have investigated the level of riskof histological subgroups, our study concludes that the link between breast cancer risks and reproductivefactors is vary depending on the histological structure of the tumor.